The impact of editorial policies and journal models on the number of articles on social humanities and communication studies related to Covid-19; Evidence from international and Indonesian scholarly work - Mahfud Anshori; Henricus Hans Setyawan Prabowo (Universitas Negeri Yogyakarta, 2021)
This study examines scientific publications during a pandemic through bibliometric network analysis. We explored three different journal databases to map COVID-19 research in humanities and social sciences, then zoom in to communication studies. Government policy, e-learning, anxiety, economic impact are popular keywords in international and Indonesian articles on Social and Humanities, while disinformation, health communication, behavior change, and literacy are more prominent in communication articles. The researcher chose the keyword occurrence analysis as the basis for mapping the research theme. The bibliographic network was deployed in three strategies to obtain keyword data co-occurrence from research abstracts, keywords from researchers, and coder's approval keywords. Lastly, Vos viewer is used to creating macro and detailed perspective networks for interpretation. The results show that journal policies and models affect the number of COVID-19 publications in the journal. Finally, this study provides an overview that normative theory and behaviorism play a role in social and communication research.